The Presidency and Public Policy Making - Edwards, George C. (University of Pittsburgh Press, 1985)
The premise behind this book is that policy making provides a useful perspective for studying the presidency, perhaps the most important and least understood policy-making institution in the United States. The eleven essays focus on diverse aspects of presidential policy making, providing insights on the presidency and its relationship to other policy-making actors and institutions.